Nihongo Speech Trainer: A Pronunciation Training System for Japanese Sounds - Tanporn Trakantalerngsak (National Research University Higher School of Economics, 2019)
This article will present the methodology, as well as the results, of a pilot study of the 'Nihongo Speech Trainer' aimed at helping Thai learners improve their ability to identify Japanese contrasts. The pilot study was performed on 15 participants. The tool focuses on specific contrasts that are problematic for Thai learners such as Japanese fricatives and affricates. Perceptual training uses a high-variability phonetic training method (hereafter referred to as "HVPT perceptual training"). Each training session included 90 minimal pairs in which the target contrasts were embedded in initial, medial and final positions. The training stimuli were produced by seven Japanese native speakers. The results of the pilot study showed that the use of the Nihongo Speech Trainer can lead to better perception of the trained Japanese sounds. The results of a questionnaire among the participants also showed that the system helped to improve their perception and production ability. However, despite these positive results with the use of the Nihongo Speech Trainer, there is room for improvement, which may lead to better training results.